Observation of halogen species in the Amundsen Gulf, Arctic, by active long-path differential optical absorption spectroscopy - Pöhler, Denis; Vogel, Leif; Frieß, Udo; Platt, Ulrich (Proceedings of the National Academy of Sciences of the United States of America, 2010)
In the polar tropospheric boundary layer, reactive halogen species (RHS) are responsible for ozone depletion as well as the oxidation of elemental mercury and dimethyl sulphide. After polar sunrise, air masses enriched in reactive bromine cover areas of several million square kilometers. Still, the source and release mechanisms of halogens are not completely understood. We report measurements of halogen oxides performed in the Amundsen Gulf, Arctic, during spring 2008. Active long-path differential optical absorption spectroscopy (LP-DOAS) measurements were set up offshore, several kilometers from the coast, directly on the sea ice, which was never done before. High bromine oxide concentrations were detected frequently during sunlight hours with a characteristic daily cycle showing morning and evening maxima and a minimum at noon. The, so far, highest observed average mixing ratio in the polar boundary layer of 41 pmol/mol (equal to pptv) was detected. Only short sea ice contact is required to release high amounts of bromine. An observed linear decrease of maximum bromine oxide levels with ambient temperature during sunlight, between -24 °C and -15 °C, provides indications on the conditions required for the emission of RHS. In addition, the data indicate the presence of reactive chlorine in the Arctic boundary layer. In contrast to Antarctica, iodine oxide was not detected above a detection limit of 0.3 pmol/mol.
Gesehen am 04.05.2023